1994
DOI: 10.1002/bin.2360090405
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal threats and behavior in a person with developmental disabilities: Effective psychiatric monitoring based on a fundamental assessment

Abstract: A psychiatric monitoring procedure was designed to better manage and treat suicidal behavior and threats in a person with moderate mental retardation, and psychiatric disorders. During the baseline suicidal threats and behavior were managed by assigning the person a counselor available to discuss his problems, keeping him in eyesight at all time, admission to the state school infirmary, counseling from his physician, and admission to a Multiple Disabilities Unit (MDU) located in a state hospital located 2 hr d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…42,43 Other small N experiments have successfully implemented packages of behavioural interventions, such as modelling, self-monitoring, and social reinforcement, 44,45 and one nonexperiment has reported the application of contingency management to prevent suicidal behaviour. 46 Finally, one dissertation 47 reported an experimental evaluation of social skills training in adolescents with autism (but not clinical depression), which observed reductions in self-reports of depression and anxiety only in the experimental group. Currently, there is no systematic review or meta-analysis of this literature and thus the status of behavioural interventions for depression for people with DDs is uncertain.…”
Section: Applied Behaviour Analysismentioning
confidence: 99%
“…42,43 Other small N experiments have successfully implemented packages of behavioural interventions, such as modelling, self-monitoring, and social reinforcement, 44,45 and one nonexperiment has reported the application of contingency management to prevent suicidal behaviour. 46 Finally, one dissertation 47 reported an experimental evaluation of social skills training in adolescents with autism (but not clinical depression), which observed reductions in self-reports of depression and anxiety only in the experimental group. Currently, there is no systematic review or meta-analysis of this literature and thus the status of behavioural interventions for depression for people with DDs is uncertain.…”
Section: Applied Behaviour Analysismentioning
confidence: 99%
“…Although other correlational studies have confirmed the association between poor social skills and other factors related to depression in people with ID, no experimental analyses of depressed behavior in people with ID have been published. However, there are a few intervention studies indicating that the behavioral characteristics of depression, such as poor eye contact, lack of speech , psychosomatic complaints (Matson, 1984), and suicidal threats (Sturmey, 1995a(Sturmey, , 1995b can be effectively reduced through various combinations of reinforcement of appropriate speech and prosocial behaviors, and through role-play, modeling, feedback, and contingency management. There is also some evidence that cognitive behavior therapy may be effective for people with mild ID and depression (Lindsay, Howells, & Pitcaithly, 1993;Sturmey, 2004).…”
Section: Functional Analysis and Dual Diagnosismentioning
confidence: 99%
“…Another example, of such a potential conflict, might be that every time a client makes a suicide threat a psychiatrist might insist on conducting an assessment of suicide risk. During this assessment the psychiatrist might attempt to persuade the client not to kill himself or herself, and then place them on one-to-one staffing for at least 24 h. In contrast, a behavioral assessment might indicate that suicide threats are maintained by attention from medical and nursing staff (Sturmey, 1995a(Sturmey, , 1995b. Good team functioning and careful case management skills are needed to integrate conflicting recommendations.…”
Section: Integration Of Psychiatric and Behavioral Formulations In Trmentioning
confidence: 99%
See 1 more Smart Citation
“…1993 ), depression ( Nezu . 1995 ), and suicidal tendencies ( Benson & Lamar 1988; Sturmey 1994) have been identified among people with an intellectual disability.…”
Section: Introductionmentioning
confidence: 99%